Deriving site-specific and time-varying supply curves for forest carbon storage. Issue 12 (14th October 2020) - Cho, Seong-Hoon; Ayara, Amine Ben; Lambert, Dayton M.; Clark, Christopher D.; Chen, Guangsheng; Hayes, Daniel J.; Sharma, Bijay P.
Abstract : We examine whether site-specific and time-varying supply functions for environmental benefits can be used to improve the design of conservation programs. We derive time-varying supply curves for site-specific forest carbon storage at the one-km 2 pixel level for three periods for the southern Appalachian region of the United States. We couple a land use model with a carbon simulation model to estimate the opportunity cost of sequestering forest carbon and derive supply curves for forest carbon storage for the three periods. Our study derives a large number of annual supply curves for site-specific forest carbon storage across multiple periods. Our approach signifies the value of identifying cost-effective approaches at a fine enough scale to account for the information asymmetry between private landowner costs and their benefits from potential land uses. The temporal aspect of our findings raise important questions about temporal flexibilities of payment designs with regard to their spatial targeting.